Coronary atherosclerosis burden, but not transient troponin elevation, predicts long-term outcome in recreational marathon runners - Moehlenkamp, Stefan; Leineweber, Kirsten; Lehmann, Nils; Braun, Siegmund; Roggenbuck, Ulla; Perrey, Mareike; Broecker-Preuss, Martina; Budde, Thomas; Halle, Martin; Mann, Klaus; Joeckel, Karl-Heinz; Erbel, Raimund; et al. (Basic research in cardiology, 2014)
We determined the prognostic value of transient increases in high-sensitive serum troponin I (hsTnI) during a marathon and its association with traditional cardiovascular risk factors and imaging-based risk markers for incident coronary events and all-cause mortality in recreational marathon runners. Baseline data of 108 marathon runners, 864 age-matched controls and 216 age- and risk factor-matched controls from the general population were recorded and their coronary event rates and all-cause mortality after 6 ± 1 years determined. hsTnI was measured in 74 marathon finishers before and after the race. Other potential predictors for coronary events, i.e., Framingham Risk Score (FRS), coronary artery calcium (CAC) and presence of myocardial fibrosis as measured by magnetic resonance imaging-based late gadolinium enhancement (LGE), were also assessed. An increase beyond the 99 % hsTnI-threshold, i.e., 0.04 μg/L, was observed in 36.5 % of runners. FRS, CAC, or prevalent LGE did not predict hsTnI values above or increases in hsTnI beyond the median after the race, nor did they predict future events. However, runners with versus without LGE had higher hsTnI values after the race (median (Q1/Q3), 0.08 μg/L (0.04/0.09) versus 0.03 μg/L (0.02/0.06), p = 0.039), and higher increases in hsTnI values during the race (median (Q1/Q3), 0.05 μg/L (0.03/0.08) versus 0.02 μg/L (0.01/0.05), p = 0.0496). Runners had a similar cumulative event rate as age-matched or age- and risk factor-matched controls, i.e., 6.5 versus 5.0 % or 4.6 %, respectively. Event rates in runners with CAC scores <100, 100-399, and ≥400 were 1.5, 12.0, and 21.4 % (p = 0.002 for trend) and not different from either control group. Runners with coronary events had a higher prevalence of LGE than runners without events (57 versus 8 %, p = 0.003). All-cause mortality was similar in marathon runners (3/108, 2.8 %) and controls (26/864, 3.0 % or 5/216, 2.4 %, respectively). Recreational marathon runners with prevalent myocardial fibrosis develop higher hsTnI values during the race than those without. Increasing coronary artery calcium scores and prevalent myocardial fibrosis, but not increases in hsTnI are associated with higher coronary event rates. All-cause mortality in marathon runners is similar to that in risk factor-matched controls. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiovascular events; Coronary artery calcium; Marathon; Prognosis; Troponin